Особенности репрезентации национально-исторических идентичностей в официальном дискурсе президентов Украины и России - Середа, В. (Социология: теория, методы, маркетинг, 2006)
The article is focused on the process of construction of an official model of historical past on the base of analysis of speeches of two Presidents of Ukraine (L.Kuchma and V.Yushchenko) and President of Russia (V.Putin) for the last decade (1994–2006). The researcher examines what kind of historical schemes (including historical commemorations, events, and heroes) was employed by each president in order to form a collective historical identity, as well as compares them. One of the key issues is to what extent Ukrainian and Russian ruling elites tried to create a historical rupture with cultural and political heritage of the Soviet past and encouraged the “revival” of some elements of pre-Soviet historical and other national traditions as well as formation of new ones.